Why the Dreyfus Affair matters - Begley, Louis (Why X matters., 2009)
In December 1894, Captain Alfred Dreyfus, a brilliant French artillery officer and a Jew of Alsatian descent, was court-martialed for selling secrets to the German military attaché in Paris based on perjured testimony and trumped-up evidence. The sentence was military degradation and life imprisonment on Devil's Island, a hellhole off the coast of French Guiana. Five years later, the case was overturned, and eventually Dreyfus was completely exonerated. Meanwhile, the Dreyfus Affair tore France apart, pitting Dreyfusards - committed to restoring freedom and honor to an innocent man convicted of a crime committed by another - against nationalists, anti-Semites, and militarists who preferred having an innocent man rot to exposing the crimes committed by ministers of war and the army's top brass in order to secure Dreyfus's conviction.